2005
DOI: 10.1021/jf051510l
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Herbicidal Evaluation of Novel 3-[(α-Hydroxy-substituted)benzylidene]pyrrolidine-2,4-diones

Abstract: A series of 3-[(alpha-hydroxy-substituted) benzylidene]pyrrolidine-2,4-dione derivatives were synthesized as candidate herbicides by reacting different aroyl acetates with N-substituted glycine esters. The new compounds were identified by 1H NMR spectroscopy and elemental analyses. Their herbicidal activities were evaluated. Some compounds exhibited excellent herbicidal activities at a dose of 187.5 g/ha. A suitable electron-donating substituent at the 2- and/or 4-position of the phenyl ring was essential for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
38
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 9 publications
1
38
0
1
Order By: Relevance
“…The title compounds were screened for herbicidal activity against B. campestris and E. crus-galli using a previously reported procedure [20,21], and the data of herbicidal activity were listed in Table 1. It was found that the title compounds are well tolerated in two weeds during the bioassay procedure.…”
Section: Resultsmentioning
confidence: 99%
“…The title compounds were screened for herbicidal activity against B. campestris and E. crus-galli using a previously reported procedure [20,21], and the data of herbicidal activity were listed in Table 1. It was found that the title compounds are well tolerated in two weeds during the bioassay procedure.…”
Section: Resultsmentioning
confidence: 99%
“…Table 2 showed that the trifluoromethylated ones (8) have some herbicide activity against monocotyledonous Echinochloa crus-galli L. Beauv (barnyard grass), which was valued by using the reported procedure (the inhibition of the seeding growth of barnyard grass) [39,40]. Due to the continuing evolution of herbicide resistance in agriculture, discovery of new herbicides such as potent barnyard grass inhibitors is important to widen its structural diversity that might possess new mode of action and then lack resistance to the currently used chemicals [41,42].…”
Section: Resultsmentioning
confidence: 99%
“…Up to now, multifarious tenuazonic acid derivatives have been synthesized to screen out new compounds with biological activity. For example, a series of 3-(α-hydroxy-benzylidene)pyrrolidine-2,4-dione derivatives were reported displaying high herbicidal activity, 12 another kind of tenuazonic acid derivatives with oxime ether moiety were presented showing obvious herbicidal and antifungal activities simultaneously. 13 As an important kind of pesticides the oxime ether derivatives have been applied as insecticides, fungicides, and herbicides.…”
Section: Introductionmentioning
confidence: 99%